Education of Hypno-parenting Method on Successfulness of Toilet Learning of Toddlers - Wahyuningsih Safitri (P3M Universitas 'Aisyiyah Surakarta, 2021)
Stages of child development tasks that must be achieved at toddler age are toilet learning. Toilet learning is an effort to train children to be able to control bowel movements and urination. Education about toilet learning can be done using the hypno-parenting method. The purpose of this study was to determine the effect of hypno-parenting health education methods on the success of toilet learning in toddler age children. This research is a quantitative study, with a quasi-experimental research design with pre-test and post-test nonequivalent control group. The sampling technique is done by using non probability sampling technique with the number of research respondents as many as 44 children. The toilet learning success measurement tool in this study used the toilet learning success questionnaire. Data analysis in this study used the Wilcoxon and Mann Whitney tests because the data were not normally distributed. The results showed that p value 0,000 <0.05 then H0 was rejected and Ha was accepted so there was an influence of hypno-parenting health education method on the success of toilet learning in toddler age children.